Solution-grown ternary quasi-cube AgSbTe2 and its optoelectronic performance for broadband photodetection. Issue 15 (22nd March 2023) - Li, Cunxin; Xu, Kaijia; Cheng, Lanjun; Wu, Zhichuan; Qian, Yinyin
Abstract : Quasi-cube AgSbTe2 nanocrystals with a representative NaCl-type crystal structure, synthesized by an eco-friendly colloidal synthetic route, exhibit good photoresponse to wide-range optical signals from 405 to 980 nm. Abstract : Group I–V–VI2 nanocrystals have been considered as potential candidates in the field of optoelectronics due to their highly tunable semiconductor characteristics. AgSbTe2, one of the emerging group I–V–VI2 nanocrystals with optical phase-change properties, a high light absorption coefficient and wide spectral response, is attractive for eco-friendly photodetector devices. However, a colloidal synthetic route for obtaining highly crystalline AgSbTe2 nanocrystals with low toxicity precursors, which is vital to high-performance solution-processed photodetector devices, is still rare. Herein, we investigate the colloidal synthesis of quasi-cube AgSbTe2 nanocrystals from the reaction of commercially available AgNO3 with Sb(Ph)3 in oleylamine at 190 °C, followed by the injection of a tellurium source, which was prepared by directly dissolving TeO2 in 1-dodecanethiol. Simple AgSbTe2 /ITO heterostructure photodetectors were fabricated by a low-temperature colloidal synthetic route in combination with the spin-coating technique, which exhibit good photoresponse in a wide range from 405 to 980 nm with fast response times (0.49 and 0.58 s) and excellent stability. This work suggests that ternary silver-based I–V–VI2 compound nanostructures have great potential for high-performance optoelectronic applications.